Analisa Hubungan Lingkungan, APD dan Pengalaman Kerja Terhadap Kecelakaan Kerja pada Fabrikasi Konstruksi Baja Proyek Pabrik Kelapa Sawit - Fahmi Firdaus Alrizal; Siti Choiriyah; Rahmad Andri Ifandi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
Occupational safety and health are very important instruments in the process of steel construction work, expecially in fabrication. In the construction of oil palm mills with steel construction for fabrication items that are often possibility to work accidents, so there is no need for one work item that can get an exemption, both in the process of cutting, moving, welding, and the packaging process of steel material used. PT Boma Bisma Indra (Persero) in the palm oil mill (CPO) steel construction fabrication project. This research was conducted with a non-probability sampling method and conducted with regression. Based on the results of the study can be known about the influence of Environmental variables, personal protective equipment (PPE) and the experience of workers on work accidents.